Chloroplast Dna Sequences Confirmed Genetic Divergence Within Calypogeia Muelleriana (Calypogeiaceae, Marchantiophyta) - Buczkowska, Katarzyna; Gonera, Patrycja; Bączkiewicz, Alina; Rosadziński, Stanisław; Rabska, Mariola (Biodiversity: Research and Conservation, 2015)
Nine species of the genus Calypogeia Raddi are currently known from Europe: C. azurea, C. integristipula, C. neesiana,C. suecica, C. muelleriana, C. sphagnicola, C. fissa, C. arguta, and C. azorica. Recently, another species, morphologically resembling C. muelleriana but genetically distinct from it, was detected using isozyme markers. In the present study, relationships between the newly detected species (C. sp. nov.) and typical C. muelleriana were analyzed using the DNA sequencesdata of three regions from the chloroplast genome: introns of trnG and trnL genes and intergenic spacer trnH-psbA. Calypogeia sp. nov. differs from C. muelleriana s. str. (typical form) in all examined chloroplast regions. It differs as well from C. azurea, which was used as a reference species. The number of fixed nucleotide differences between C. muelleriana s. str. and C. sp. nov. is almost the same as between C. muelleriana s. str. and C. azurea. The results of the present study suggest a closer affinity of C. sp. nov. to C. azurea than to C. muelleriana s. str. in Europe, C. muelleriana s. str. was noted in Poland, Germany, Holland, United Kingdom and Azores. Samples determined as C. sp. nov., besides Poland, were so far detected also in North America